2013
DOI: 10.1016/j.cub.2013.03.044
|View full text |Cite
|
Sign up to set email alerts
|

ANGUSTIFOLIA3 Signaling Coordinates Proliferation between Clonally Distinct Cells in Leaves

Abstract: Coordinated proliferation between clonally distinct cells via inter-cell-layer signaling largely determines the size and shape of plant organs. Nonetheless, the signaling mechanism underlying this coordination in leaves remains elusive because of a lack of understanding of the signaling molecule (or molecules) involved. ANGUSTIFOLIA3 (AN3, also called GRF-INTERACTING FACTOR1) encodes a putative transcriptional coactivator with homology to human synovial sarcoma translocation protein. AN3 transcripts accumulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
130
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(143 citation statements)
references
References 21 publications
12
130
0
1
Order By: Relevance
“…The mRNA expression domain of the AN3/ AtGIF1 is, however, restricted to inner tissue but not in epidermis in the leaf primordia (Kawade et al 2013). Detailed analyses of the an3 mutant showed that both the epidermis and inner tissue are under a control of the AN3/AtGIF1 activity, in terms of number of cells.…”
Section: Outline Of Events In Arabidopsis Leaf Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The mRNA expression domain of the AN3/ AtGIF1 is, however, restricted to inner tissue but not in epidermis in the leaf primordia (Kawade et al 2013). Detailed analyses of the an3 mutant showed that both the epidermis and inner tissue are under a control of the AN3/AtGIF1 activity, in terms of number of cells.…”
Section: Outline Of Events In Arabidopsis Leaf Developmentmentioning
confidence: 99%
“…The apical part of the leaf primordium is occupied by small, non-polarized cells with longitudinal, transverse, and oblique arrangements of crosswalls relative to the proximal-distal axis. The basal part of the leaf primordium has large, longitudinally polarized cells that are arranged paral- protein moves from inner tissue to epidermis thereby coordinating cell proliferation between different tissue layers; interference with AN3 movement results in abnormal leaf size and shape, indicating that AN3 signaling is indispensable for normal leaf development with a coordinated growth between epidermis and inner tissue (Kawade et al 2013). This is the first report on the importance of the role of mesophyll layers as a signaling source for the coordinated cell proliferation in a leaf primordium.…”
Section: Outline Of Events In Arabidopsis Leaf Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Lamina growth also requires coordination between the epidermis and the mesophyll layers, and it was recently shown that the transcriptional co-activator ANGUSTIFOLIA3 (AN3) is produced only in mesophyll cells but moves into the epidermis to promote growth in both layers (Kawade et al, 2013). AN3 was subsequently shown to modulate transcription through interaction with chromatinremodeling factors (Vercruyssen et al, 2014).…”
Section: The Mechanics Of Leaf Initiationmentioning
confidence: 99%
“…For example, by considering the manner through which a cell reaches its ultimate size and performing kinematic analyses of cell size dynamism, three classes of compensation have been identified: Class I, an enhanced postmitotic cell expansion rate (seen in angustifolia [an]3-4, fugu2-1/fasciata [fas]1-5, and erecta [er]-102); Class II, an extended post-mitotic cell expansion period (seen in fugu5-1); and Class III, increase in the size of dividing cells (seen in KIP-RELATED PROTEIN 2 [KRP2] over-expressing cells) (Ferjani et al 2007(Ferjani et al , 2008(Ferjani et al , 2010(Ferjani et al , 2013a(Ferjani et al , 2013b(Ferjani et al , 2014. Furthermore, during compensation, cell-autonomous and non-cell-autonomous pathways have been identified (Kawade et al 2010, 2013, Ferjani et al 2013a. Finally, the fact that compensation occurs in a wide range of plant species other than Arabidopsis, including tobacco, rice, and snapdragon, suggests that common developmental mechanisms that trigger compensation are widely conserved in angiosperms (Hemerly et al 1995, Barrôco et al 2006, Delgado-Benarroch et al 2009.…”
Section: Introductionmentioning
confidence: 99%